Strategic signals in the app economy: an empirical study of Google Play Store - Shao, Jianhua (2016)
The dominance of Android and iOS have created a duopoly in the smartphone market. In this context, both Android and iOS need to select high quality apps from its massive number of app developers to recommend to app consumers. Generally speaking, when the market is small, the platform like Android and iOS can allocate resources to manual test the app quality for selection; but as the market size increased, the required resource for selection is also increased and would challenge the platform’s capability, thus the platform faces the selection difficulty. Unlike iOS, Android adopts an open strategy to compete against iOS for innovative developers. This strategy has led to inadvertent consequences including: "fragmentation" issues, weakened governance power, entry of non-competent developers and, notably, vetting of the quality of apps and developers.